The EUROclass trial: defining subgroups in common variable immunodeficiency - Wehr, Claudia; Kivioja, Teemu; Schmitt, Christian; Ferry, Berne; Witte, Torsten; Eren, Efrem; Vlková, Marcela; Hernandez, Manuel; Detkova, Drahomira; Bos, Philip R; Poerksen, Gonke; von Bernuth, Horst; et al. (Blood, 2008)
The heterogeneity of common variable immunodeficiency (CVID) calls for a classification addressing pathogenic mechanisms as well as clinical relevance. This European multicenter trial was initiated to develop a consensus of 2 existing classification schemes based on flowcytometric B-cell phenotyping and the clinical course. The clinical evaluation of 303 patients with the established diagnosis of CVID demonstrated a significant coincidence of granulomatous disease, autoimmune cytopenia, and splenomegaly. Phenotyping of B-cell subpopulations confirmed a severe reduction of switched memory B cells in most of the patients that was associated with a higher risk for splenomegaly and granulomatous disease. An expansion of CD21(low) B cells marked patients with splenomegaly. Lymphadenopathy was significantly linked with transitional B-cell expansion. Based on these findings and pathogenic consideration of B-cell differentiation, we suggest an improved classification for CVID (EUROclass), separating patients with nearly absent B cells (less than 1%), severely reduced switched memory B cells (less than 2%), and expansion of transitional (more than 9%) or CD21(low) B cells (more than 10%). Whereas the first group contains all patients with severe defects of early B-cell differentiation, severely reduced switched memory B cells indicate a defective germinal center development as found in inducible constimulator (ICOS) or CD40L deficiency. The underlying defects of expanded transitional or CD21(low) B cells remain to be elucidated. This trial is re-gistered at http://www.uniklinik-freiburg.de/zks/live/uklregister/Oeffentlich.html as UKF000308.
Keywords: dospělí; homeostáza; Female; Europe; průtoková cytometrie; Adult; ženské pohlaví; běžná variabilní imunodeficience; lidé; Evropa; Homeostasis; Flow Cytometry; konsensus; Immunoglobulins; Immunophenotyping; kohortové studie; Consensus; Common Variable Immunodeficiency; Cohort Studies; imunofenotypizace; Male; B-Lymphocytes; B-lymfocyty; lidé středního věku; imunoglobuliny; mužské pohlaví; Middle Aged; Humans